Mass evacuations: learning from the past - Briggs, C (Refugee Studies Centre, University of Oxford, 2015)
Twenty years after the evacuations from the Bosnian ‘safe areas’, humanitarians continue to struggle with dilemmas around humanitarian evacuations.